Using microtensiometers and other on-the-ground and remote sensing tools to determine olive trees water status - Ramírez-Cuesta, Juan M.; Pérez-Pérez, Juan G.; Badal, Eduardo; Bonet, Luis; Vanella, Daniela; Tasa, María; Intrigliolo, Diego S. (ISHS, 2024)
Determining tree water status is of importance for scheduling irrigation and for other field management operations. Stem water potential (SWP) is considered as the standard indicator, but this determination cannot be automated. In the present research, we evaluated the usefulness of a new microtensiometer sensor named FloraPulse® (FP) by comparing it with several determinations of the orchard soil-plant-atmosphere continuum. FP sensors were inserted into tree main trunks and concomitant occasional determinations of SWP were carried out. The study was conducted during 2022 with olive trees, in two experiments: (i) pot conditions, where we evaluated FP response to short-term variation in soil water status and changes in the evaporative demand; and (ii) an olive orchard under two irrigation regimes. With the dataset obtained from the potted olive experiment, a multi linear regression analysis among SWP, soil water content (SWC) and weather parameters was obtained. The results of the comparison between the SWP values derived by both methods showed the same pattern, although SWP determined under pot conditions with the pressure chamber was more sensitive to changes in crop water status than the FP readings. In addition, the relationship between FP and SWP varied among the experimental trees used in the experiment. On a tree-to-tree basis, there was in general a tight relationship between FP and SWP, but when pooling data from all trees together, the correlation between the types of determinations was much weaker. In summary, FP sensors seems a promising new tool to monitor tree water status, but probably more in relative terms and with the objective to determine the diurnal and seasonal variations in water status. For robust absolute determinations of actual SWP, sensors might require local calibration. The experiment is still on-going in order to evaluate sensor responses more in the long-term (i.e. more than a single season).